'Walking the talk': Applying community‐based social marketing to a pilot food waste programme at Lincoln Park Zoo. Issue 5 (4th September 2022) - Shoffstall, Erin J.; Somor, Julie L.
Abstract: Zoos and aquariums are uniquely situated to encourage the adoption of pro‐environmental behaviours by the public at large. While the activation of conservation behaviours in a visitor base is necessary, there is an equally essential call to 'walk the talk' by aligning organizational missions and identity with internal practice. This study evaluated an adapted community‐based social marketing (CBSM) model to foster food waste‐related behaviour change in a unique audience of zoo staff and volunteers. This paper describes an innovative, real‐world example of how conservation institutions can modify conservation psychology theories and the CBSM framework for the practical application of mission‐aligned pro‐environmental behaviour change campaigns. While audience engagement fluctuated throughout the campaign, we observed an attitudinal and/or behavioural shift in our target audience as a result of the campaign, indicating some success in achieving positive outcomes. The implications of these findings are discussed and recommendations are made about how to sustain momentum and participation in campaigns, including the utility of a scale for engagement approaches relative to organizational capacity and resources available. Abstract : Adapted community‐based social marketing model mapped with our process and recommendations to increase campaign engagement at specific stages (blue boxes). The box on the right shows a possible framework for adjusting audience engagement based on organizational capacity and resources available. Research highlights: Participants took action beyond the target behaviour, indicating there was a positive spillover effect as a result of the campaign intervention. Adaptation of the community‐based social marketing framework may offer institutions with limited capacity and resources an opportunity to apply science‐based models.